Supply chain security : a comprehensive approach - Arway, Arthur G. (CRC Press, 2013)
The supply chain is a complex system of numerous, integrated stakeholders. These stakeholders are responsible for the transportation, storage, documentation, and handling of material goods and cargo. Each entity has its own unique relationship with and role within the chain-as well as its own unique security requirements. The challenge of trying to secure the supply chain at every level is both a domestic and global concern. In this global economy, companies must be able to integrate security into supply chain logistics to protect their employees, assets, and clients from incidents of theft and other damaging events. Supply Chain Security: A Comprehensive Approach provides security professionals the tools necessary to ensure supply chain security. The book demonstrates how to establish and enforce security policies and protocols, including rapid responses that must be deployed in the event of a theft or security incident. Most importantly, it enables professionals to integrate business practices into the planning, development, and successful operation of supply chains to ensure security and protect assets. Drawn from the experience of a recognized leader in domestic and international supply chain logistics, trade, and transportation security, the book illustrates through a series of case studies how security professionals can institute sound security practices. By demonstrating to their stakeholders and potential customers that they provide a secure environment for materials, products, goods, and cargo, companies can increase their customer base and improve their bottom line.- Resumé vydavatel
Keywords: dopravní logistika; přeprava zboží; bezpečnostní management; transportation logistics; goods transportation; safety management; příručky; případové studie; handbooks, manuals, etc; case studies; elektronické knihy; electronic books